Ignacio Ellacuría’s Theology of Liberation Under Debate with Joseph Ratzinger and Michael Novak (Andamios, Revista de Investigación Social, 2024)
This article carries out the analysis and understanding of Ignacio Ellacuría’s liberation theology starting from two moments: his response to Joseph Ratzinger’s Instruction on some aspects of “liberation theology”, as well as the critique and reading of the same by the theologian of capitalism Michael Novak –an influential figure in the libertarian liberals such as Javier Milei– and the reading of the historical Jesus as of liberation in the Old Testament. This with the aim of highlighting the praxis of Christianity in the author, as well as its relevance for our present time.
Keywords: Liberation theology; historical logos; theology of creativity; Ignacio Ellacuría; Michael Novak